Enhancing esthetics from growth modification - Halim, Himawan; Halim, Ivan Anthony (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
Alteration of maxillary growth, improvement in mandibular growth and position, and change in dental and muscular relationships, especially changing in esthetic profile are the expected results of myofunctional appliances. The use of Bionator appliance is a widely used myofunctional appliance for the management of Class II malocclusion. A normal and healthy Indonesian boy aged 12 years and 2 months old was motivated for treatment for protruded maxillary anterior teeth and retrognathic mandibular. He was introverted and had poor self-esteem despite his normal medical history. He had a Class II Division 1 malocclusion with a 10 mm overjet, normal overbite, with an SNA of 92.89°, SNB of 85.32°, ANB of 7.52°, and a facial angle of 88.11°. He was in mixed dentition stage with all his permanent teeth available and ready to erupt. The patient was treated in two phases: phase I to correct the skeletal discrepancy using Bionator appliance and phase II to correct the tooth discrepancy using fixed appliance. At the end of phase I treatment, or 10 months of wearing Bionator appliance, the patient’s mandible was positioned forward with the ANB angle reduced from 7.56° to 2.30°, and the profile was greatly improved. His molar and canine relationship was Class I. His profile became straight and more favorable. Early treatment using functional appliance therapy can reduce the severity of Class II skeletal pattern and instant change in facial and dental appearance in growing patients.